2021
DOI: 10.1088/1741-2552/ac3207
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between stimulation focality and the number of coils in multi-locus transcranial magnetic stimulation

Abstract: Objective. Coils designed for transcranial magnetic stimulation (TMS) must incorporate trade-offs between the required electrical power or energy, focality and depth penetration of the induced electric field (E-field), coil size, and mechanical properties of the coil, as all of them cannot be optimally met at the same time. In multi-locus TMS (mTMS), a transducer consisting of several coils allows electronically targeted stimulation of the cortex without physically moving a coil. In this study, we aimed to inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…For example, the 30-mm targeting range in the cortex can be made larger or E-field focality can be made adjustable. To expand the cortical region within which the E-field can be targeted beyond the 30-mm-diameter region demonstrated in this study, one may (1) develop a transducer with more than five coils [9,40], (2) reduce the desired E-field focality to design a five-coil transducer with a wider control region [40], or (3) implement a transducer that follows the head curvature [40]. To study interhemispheric communication in motor networks for the study of motor control [41], one may use the 5-coil transducer on one hemisphere while stimulating the contralateral hemisphere with a separate figureof-eight coil.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the 30-mm targeting range in the cortex can be made larger or E-field focality can be made adjustable. To expand the cortical region within which the E-field can be targeted beyond the 30-mm-diameter region demonstrated in this study, one may (1) develop a transducer with more than five coils [9,40], (2) reduce the desired E-field focality to design a five-coil transducer with a wider control region [40], or (3) implement a transducer that follows the head curvature [40]. To study interhemispheric communication in motor networks for the study of motor control [41], one may use the 5-coil transducer on one hemisphere while stimulating the contralateral hemisphere with a separate figureof-eight coil.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the 30-mm targeting range in the cortex can be made larger or E-field focality can be made adjustable. To expand the cortical region within which the E-field can be targeted beyond the 30-mm-diameter region demonstrated in this study, one may (1) develop a transducer with more than five coils [ 9 , 40 ], (2) reduce the desired E-field focality to design a five-coil transducer with a wider control region [ 40 ], or (3) implement a transducer that follows the head curvature [ 40 ]. To study interhemispheric communication in motor networks for the study of motor control [ 41 ], one may use the 5-coil transducer on one hemisphere while stimulating the contralateral hemisphere with a separate figure-of-eight coil.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research exploring rTMS protocols revealed its strength for treatmentresistant depression symptomology, lessening chronic orofacial pains, and obsessive-compulsive disorder, among several other ailments [22][23][24]. A hallmark characteristic of rTMS is its depthfocality tradeoff, which results in stimuli applied to non-targeted brain structures when probing deeper regions [25,26]. This feature seems to suggest that rTMS may prove highly efficacious in repairing dysfunctional neural networks (via activity-dependent modulation of synaptic plasticity), particularly in TBI patients with diffuse axonal injury.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%